Performance and emissions of a gas turbine engine using ox tallow ethyl-ester blended with kerosene - Silva, Ramon E. P.; Lacava, Pedro T.; Carvalho, Joao A. [UNESP] (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2014)
The performance and emissions behavior of a Rover 1S/60 turboshaft engine when operated with several blends of aviation kerosene and ox tallow ethyl-ester are shown in this article. The tests were performed with a compressor shaft coupled to an hydraulic dynamometer where data of power and mass fuel flow were collected to determine the brake specific fuel consumption. A flue gas analyzer was positioned at the exhaust duct to collect oxygen, carbon dioxide, carbon monoxide and nitrous oxides. An increase in the specific fuel consumption was observed due to the lesser lower heating value of the most oxygenated blends. However, reductions of CO, CO2 and NO (x) have been observed and no-significant ill effects have occurred in the turbine operation.
Keywords: Ethyl-ester; Gas turbine; Pollutant emissions; Biodiesel